Deterministic seismic risk assessment in the city of Aigion (W. Corinth Gulf, Greece) and juxtaposition with real damage due to the 1995 Mw6.4 earthquake - Giannaraki, G.; Kassaras, I.; Roumelioti, Z.; D. Kazantzidou-Firtinidou; A. Ganas (2019)
Earthquake scenarios were applied towards seismic risk assessment in the earthquake prone city of Aigion (W. Corinth Gulf), by combining deterministic seismic hazard and empirical structural vulnerability. Ground motions for three hazardous fault sources for Aigion were generated using a finite source stochastic simulation technique, taking into account the well-established seismotectonics of the area and site effects derived from ambient noise horizontal-to-vertical-spectral-ratios (HVSR). Validation of the parameters of the stochastic simulation and the estimated damage was performed with respect to real recordings and the damage database of a past seismic event in the area. Vulnerability was assessed empirically for an exposure model comprising 3200 buildings, compiled with on site and remoted techniques. The European Macroseismic Scale (EMS-98) was used to describe the ground motion severity in terms of macroseismic intensity and the taxonomy of the building stock into 7 structural types. Seismic risk was spatialized using GIS mapping tools on a building block scale in terms of EMS-98 damage grades and their maximum probability of occurrence. The obtained risk assessment models indicate that the northeastern and partly the southern part of Aigion are more susceptible to damage, in accordance with damage distribution from the most recent Mw6.4 disastrous earthquake for the city in 1995, the site amplification inferred from HVSR, and the assessed vulnerability of the constructions. Nevertheless, the current building stock demonstrates significantly enhanced seismic behaviour, due to rehabilitation after the 1995 earthquake. Despite unavoidable uncertainties, intrinsic to both the method and data, the herein seismic risk assessment appears realistic and consistent, thus allowing its exploitation towards loss estimation and mitigation scenarios.